Problemas
Given xgt 0 rewrite the following expression in simplest form. sqrt [4](16x^6)cdot sqrt (144x^11) Answer Attemptiout of 2 square
Roztwór
Armando
élite · Tutor durante 8 años
4.5
(294 Votos)
Respuesta
The simplified form of the given expression is
.
Explicación
## Step 1The given expression is
. We need to simplify this expression.## Step 2We can rewrite the expression by using the property of exponents, which states that
.### \(\sqrt [4]{16x^{6}} = (16x^{6})^{1/4}\)### \(\sqrt {144x^{11}} = (144x^{11})^{1/2}\)## Step 3Next, we simplify the expression by applying the power of a power rule, which states that \((a^m)^n = a^{mn}\).### \((16x^{6})^{1/4} = 16^{1/4} \cdot (x^{6})^{1/4} = 2x^{3/2}\)### \((144x^{11})^{1/2} = 144^{1/2} \cdot (x^{11})^{1/2} = 12x^{11/2}\)## Step 4Finally, we multiply the two simplified expressions together.###